Poly[[aqua(μ(2)-oxalato)(μ(2)-2-oxidopyridinium-3-carboxylato)dysprosium(III)] monohydrate] - Huang, Chun-De (International Union of Crystallography, 2009)
In the title complex, {[Dy(C(6)H(4)NO(3))(C(2)O(4))(H(2)O)]·H(2)O}(n), the Dy(III) ion is coordinated by seven O atoms from two 2-oxidopyridinium-3-carboxylate ligands, two oxalate ligands and one water molecule, displaying a distorted bicapped trigonal-prismatic geometry. The carboxylate groups of the 2-oxidopyridinium-3-carboxylate and oxalate ligands link dysprosium metal centres, forming layers parallel to (100). These layers are further connected by intermolecular O—H⋯O hydrogen-bonding interactions involving the coordinated water molecules, forming a three-dimensional supramolecular network. The uncoordinated water molecule is involved in N—H⋯O and O—H⋯O hydrogen-bonding interactions within the layer.